On the maximum of stochastic Gaussian field - Lapinskas, R. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Лапинскас. О максимуме однородного нормального поля R. Lapinskas. Apie homogeninio normalinio lauko maksimumą